1987
DOI: 10.1038/bjc.1987.257
|View full text |Cite
|
Sign up to set email alerts
|

Survival of large bowel carcinoma patients with different DNA ploidy

Abstract: Summary One hundred patients operated for large bowel carcinoma were divided into a distinct aneuploid group of 63, and a near diploid one of 37. Flow cytometry was used for determination of the DNA ploidy pattern. All tumours in the aneuploid group contained one or more aneuploid cell populations. All patients were followed clinically from 3.5 to 7.8 years. The corrected 5 year survival was 64% and 49% for patients with near diploid and aneuploid tumours, respectively (not significant). Significant difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
24
1

Year Published

1990
1990
1996
1996

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 68 publications
(28 citation statements)
references
References 21 publications
3
24
1
Order By: Relevance
“…We have earlier reported similar proportions of aneuploidy in colorectal carcinomas from larger series of patients without ulcerative colitis (Rognum et al, 1982;1987b;Meling et al, 1991). Other studies have also reported similar proportions of aneuploid carcinomas in patients with ulcerative colitis (Hammarberg et al, 1984;Melville et al, 1988).…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…We have earlier reported similar proportions of aneuploidy in colorectal carcinomas from larger series of patients without ulcerative colitis (Rognum et al, 1982;1987b;Meling et al, 1991). Other studies have also reported similar proportions of aneuploid carcinomas in patients with ulcerative colitis (Hammarberg et al, 1984;Melville et al, 1988).…”
Section: Discussionsupporting
confidence: 60%
“…Three of them also had aneuploid cell clones in tumour-distant flat mucosa, and these three were the only patients with metastatic disease (Table II). This is, however, interesting, since aneuploid carcinomas are associated with a worse prognosis than diploid ones (Wolley et al, 1982;Armitage et al, 1985;Rognum et al, 1987b;. The aneuploid cells in the mucosa from these three patients, all had DNA indices different from 1.7, and in two of the patients, the DNA index was the same as in the main carcinoma.…”
Section: Discussionmentioning
confidence: 86%
“…Reviewing the survival curves of patients with diploid and nondiploid (aneuploid and tetraploid) tumours from various centres there is a general consistency in the survival advantage to patients with diploid tumours (Scott et al, 1987;Quirke et al, 1987;Jones et al, 1988;Jass et al, 1989). There are a number of reports which show only a borderline or no significant relation between DNA ploidy and prognosis (Bauer et al, 1987;Schutte et al, 1987;Rognum et al, 1987). In addition some reports show that although ploidy had prognostic significance in a univariate analysis this was lost in multivariant analysis (Jass et al, 1989).…”
mentioning
confidence: 99%
“…The preoperative plasma CEA level has proved valuable in follow-up studies after surgery for large bowel carcinomas (Wanebo et al, 1978;Rognum, 1986;Meling et al, 1992). During the last years several papers applying flow cytometric DNA determination methods in human solid tumours have been published, and studies have shown that the presence of distinctly aneuploid DNA ploidy pattern in large bowel carcinoma worsens survival rates significantly (Wolley et al, 1982;Rognum et al, 1987aRognum et al, , 1991.…”
mentioning
confidence: 99%